ISLAMIC RELIGIOUS EDUCATION TEACHER STRATEGIES IN IMPROVING 4C SKILLS (COMMUNICATION, COLLABORATION, CRITICAL THINKING, CREATIVITY) IN CLASS 6 STUDENTS AT SDN 2 NORTH KELAYU - muhammad rizi Fauzi (JOETAL: Journal of Education, Teaching and Learning, 2024)
This research aims to improve Islamic religious education teacher through 4C. This research is a type of qualitative research; there are two sources of data in this research, namely primary data and secondary data. For data collection using free guided interviews, observation and documentation methods. The results of this research are 1) In improving creative skills, teachers use problem based learning and project based learning models with interactive lecture methods, questions and answers and role playing (demonstrations). 2). Teacher's strategy in improving students' 4C skills in class 6 learning at SDN 2 North Kelayu can be said to be good, this is proven by the strategies implemented by the teacher, it can be seen that students have been able to follow the learning process well. Apart from that, students also become more active in the learning process, braver to express opinions, more creative in providing solutions and answers, and then can complete group assignments well. Through the application of various strategies, the results obtained are that students are able to convey their opinions well and politely, are able to exchange opinions with their friends, and are able to communicate the results of their discussions, are able to capture the material presented by the teacher, and are more creative in providing answers and solutions when The teacher reflects and asks questions and problems during the learning process. Apart from that, students are also able to improvise the roles they get when carrying out demonstrations.